Can Transformational Leadership, Work-Life Balance, Organizational Commitment, and Job Satisfaction Encourage Civil Servants' Organizational Citizenship Behavior (OCB) - Mulyanto Syawal; Ahmad Badawy Saluy; Novawiguna Kemalasari (Greenation International Journal of Tourism and Management, 2023)
Organizational Citizenship Behavior (OCB) is an essential factor in optimizing the achievement of organizational goals. The present study investigates the effect of Transformational Leadership, Work-Life Balance, and Organizational Commitment on OCB with Job Satisfaction as an intervening variable of civil servants at the Direktorat Sistem Perbendaharaan (Directorate of Treasury System), Ministry of Finance of the Republic of Indonesia. The research used a quantitative approach through questionnaires to 91 respondents on a Likert scale with analysis using the SEM-PLS (Structural Equation Modeling-Partial Least Square). The results showed: Transformational Leadership has a positive and significant effect on OCB; Work-Life Balance has a positive and insignificant effect on OCB; Organizational Commitment has a positive and insignificant effect on OCB; Job Satisfaction has a positive and significant effect on OCB; Transformational Leadership has a positive and significant effect on Job Satisfaction; Work-Life Balance has a positive and significant effect on Job Satisfaction; Organizational Commitment has a positive and significant effect on Job Satisfaction; Job Satisfaction mediates the effect of Transformational Leadership on OCB; Job Satisfaction does not mediate the effect of Work-Life Balance on OCB; Job Satisfaction mediates the effect of Organizational Commitment on OCB.